1997
DOI: 10.4141/a96-091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source of forage and level of concentrate on chewing activity and milk production response in late lactation cows

Abstract: . 1997. Effects of source of forage and level of concentrate on chewing activity and milk production response in late lactation cows. Can. J. Anim. Sci. 77: 253-258. Four cannulated Holstein cows in late lactation were used in a 4 × 4 Latin square design experiment to determine the effects of forage source with different NDF concentrations and level of concentrate on chewing activity and milk production. Diets were 65% first-cut alfalfa silage with 54% NDF and 35% concentrate, 50% alfalfa and 50% concentrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
11
1
2
Order By: Relevance
“…The ECM yield followed to some extent the concentration of CP in the ration. Previous results of Okine et al (1997) suggested that a higher milk yield could be induced by a higher CP intake and a slightly higher DMI, and NRC (2001) also concluded that an increased CP concentration in the ration increased the milk yield. Their results were based on several protein feeding trials and was true until 19% CP.…”
Section: Milk Yield and Compositionmentioning
confidence: 91%
“…The ECM yield followed to some extent the concentration of CP in the ration. Previous results of Okine et al (1997) suggested that a higher milk yield could be induced by a higher CP intake and a slightly higher DMI, and NRC (2001) also concluded that an increased CP concentration in the ration increased the milk yield. Their results were based on several protein feeding trials and was true until 19% CP.…”
Section: Milk Yield and Compositionmentioning
confidence: 91%
“…The diet of these cows was formulated to satisfy the nutrient requirements of a Holstein cow weighing 600 to 650 kg and producing 30 kg of milk daily. The diet was a 50:50 forage:concentrate ratio (DM basis) composed of a first-cut alfalfa with 54% NDF and a mixture of barley, canola and soybean meal, ground corn, molasses, and mineral-vitamin premix (Okine et al, 1997). Mammary glands were collected from two of the cows directly off the processing line at a local abattoir and from the other two slaughtered by exsanguination at the University of Alberta Research Station.…”
Section: Animals Tissue Removal and Plasma Membrane Preparationmentioning
confidence: 99%
“…However, a variation of about 4.7 % was recorded between TR1 (containing 54 % of concentrate) and the other rations. Okine et al (1997) found that lactose yield was increased by 11 % in cows fed 50 % concentrate diets compared with cows fed 35 % concentrate diets. Malossini et al (1996) found also a small but significant increase following the increase in feeding level (1.6 % with diet high feeding level (7 % of UFL above the allowances) and 1.4% with diet very high feeding level (14 % of UFL above the allowances) comparatively to normal feeding level.…”
Section: Effect Of Type Of Rationmentioning
confidence: 95%